Mortality of the population in Slovakia: past and present - Plesko, I; Zatonski, W (Central European journal of public health, 2000)
This contribution presents an analysis of the health status of the Slovakian population using trends in overall mortality, death rates from major diseases, and of other health indicators. The health status of the Slovak population at the beginning of this century as well as at the time of the establishment of Czechoslovakia in 1918 was very bad. This situation is demonstrated by the extremely high infant mortality rate, short life expectancy and enormous mortality from infectious diseases, particularly from tuberculosis. Despite progress before the Second World War, only in the postwar period was the health status comparable with other developed countries of western Europe as there was a rapid improvement of health lasting until the middle of 1960s. This positive evolution resulted mainly from the extensive use of preventive measures against infectious diseases, contributing to the decline of infant mortality and the gradual prolongation of life expectancy. A simultaneous rapid increase of noninfectious, mainly chronic diseases, particularly of cardiovascular diseases and cancer was observed. Attempts to deal with this increase lead only to enlargement of treatment facilities. The whole health policy in prevention, including the pre- and postgradual education of physicians and paramedical personnel, remained in its traditional orientation against infectious diseases. This situation, together with low social and moral standard of the population, increasing consumption of cigarettes, alcohol and inadequate composition and superfluous food led to the rapid deterioration of the health status of the Slovakian population in the past three decades. The orientation of the health policy to the prevention of noninfectious, mainly chronic, degenerative diseases and, above all a change of the attitude of the inhabitants of this country to their own health, present the only way to the substantial and rapid improvement of the health status of the population of Slovakia.
Keywords: dospělí; Infant; dítě; Mortality; Health Status Indicators; Adult; Cause of Death; Adolescent; Slovakia; lidé; ukazatele zdravotního stavu; mortalita; kojenec; Aged; lidé středního věku; Child; Slovenská republika; senioři; příčina smrti; Middle Aged; mladiství; Humans